Environmental & architectural phenomenology. Vol. 9, issue 1 - (:unkn) unknown (Kansas State University. Architecture Department, 1998)
Vol. 9, No. 1, Winter 1998 (includes “items of interest,” "citations received,” book reviews on Margaret Colquhoun & Axel Ewald's New Eyes for Plants & Henri Bortoft's Wholeness of Nature, essay by Mark Riegner, and introduction of Sir George Trevelyan's Active Eye in Architecture).
Keywords: Environmental psychology - Periodicals; Human beings - Effect of environment on - Periodicals; Architecture - Environmental aspects - Periodicals; Architecture - Human factors - Periodicals; Architecture - Psychological aspects - Periodicals; Phenomenology - Periodicals